Stress Distribution and Fluctuation Cycle on the Rack Face of the Rock Cutting Tool - Xiaofeng Yang; Yongchao Xue; Jiaheng Zhou (Shock and Vibration)
The distribution of the stress field on the rack face has significant impacts on the performance and service life of the rock cutting tool. A dynamic simulation model of the stress on the rock cutting tool is established by finite element code Abaqus, and the distribution of local stress on the rack face and its impact factors are studied. It is concluded that the local stress on the rack face of the rock cutting tool shows obvious periodical fluctuation characteristics, and the fluctuation cycle of each point on the tool remains unchanged under the same cutting conditions. The stress fluctuation cycle period decreases with the increase of cutting speed inversely. The cutting depth and the back angle of the cutting tool have no obvious impact on the stress fluctuation period. However, the cutting depth and the back angle have obvious impacts on the average stress distributions of each point on the rack face of the tool. That is, the increase of back angle and cutting depth could cause the maximum stress point of the rack face to move upward to the tool tip.